Neferine Attenuates Acute Kidney Injury by Inhibiting NF-κB Signaling and Upregulating Klotho Expression - Li, Huihui; Chen, Wenhang; Chen, Yusa; Zhou, Qiaoling; Xiao, Ping; Tang, Rong; Xue, Jing (Frontiers in Pharmacology, 2019)
Purpose: Morbidity associated with and mortality from acute kidney injury (AKI) is gradually increasing, and no efficient drug is available. We explored whether neferine, a bisbenzylisoquinoline alkaloid, attenuated AKI, and the possible mechanisms in play in vivo and in vitro. Methods: We induced AKI using ischemia-reperfusion (I/R) or lipopolysaccharide (LPS) in vivo. C57 BL/6 male mice were randomized into two groups each containing four subgroups: control, neferine, I/R or LPS, and I/R or LPS + neferine. Mice were sacrificed 24 h after AKI induction and kidneys and sera were collected. NRK-52E cells were exposed to hypoxia/reoxygenation (H/R) or LPS in vitro. Results: Neferine pretreatment significantly alleviated kidney functional loss and pathological damage. In the AKI mouse models induced by I/R or LPS, neferine inhibited the infiltration of inflammatory cells, including granulocytes and macrophages. Both in vivo and in vitro, neferine attenuated apoptosis, suppressed inflammatory cytokine production, decreased degradation of IκB-α, and inhibited nuclear translocation of NF-κB. Furthermore, it also upregulated Klotho expression in AKI. Conclusion: Neferine mitigated renal injury in AKI models, perhaps by suppressing the activation of NF-κB and upregulating the expression of Klotho.